Advanced Materials for Sodium‐Ion Capacitors with Superior Energy–Power Properties: Progress and Perspectives. Issue 15 (24th September 2019) - Zhang, Hongwei; Hu, Mingxiang; Lv, Qian; Huang, Zheng‐Hong; Kang, Feiyu; Lv, Ruitao
Abstract: Developing electrochemical energy storage devices with high energy–power densities, long cycling life, as well as low cost is of great significance. Sodium‐ion capacitors (NICs), with Na + as carriers, are composed of a high capacity battery‐type electrode and a high rate capacitive electrode. However, unlike their lithium‐ion analogues, the research on NICs is still in its infancy. Rational material designs still need to be developed to meet the increasing requirements for NICs with superior energy–power performance and low cost. In the past few years, various materials have been explored to develop NICs with the merits of superior electrochemical performance, low cost, good stability, and environmental friendliness. Here, the material design strategies for sodium‐ion capacitors are summarized, with focus on cathode materials, anode materials, and electrolytes. The challenges and opportunities ahead for the future research on materials for NICs are also proposed. Abstract : Sodium‐ion capacitors (NICs) have attracted increasing attention due to their merits in combining the high energy densities of batteries, high power densities of supercapacitors, as well as the earth‐abundant reserves of sodium. Recent progresses on advanced materials for NICs are summarized. The challenges and opportunities ahead are also proposed.